Correlations between cytoplasmic CSE1L in neoplastic colorectal glands and depth of tumor penetration and cancer stage - Tai, Cheng-Jeng (BioMed Central, 2013)
BACKGROUND: Colorectal carcinomas spread easily to nearby tissues around the colon or rectum, and display strong potential for invasion and metastasis. CSE1L, the chromosome segregation 1-like protein, is implicated in cancer progression and is located in both the cytoplasm and nuclei of tumor cells. We investigated the prognostic significance of cytoplasmic vs. nuclear CSE1L expression in colorectal cancer. METHODS: The invasion- and metastasis-stimulating activities of CSE1L were studied by in vitro invasion and animal experiments. CSE1L expression in colorectal cancer was assayed by immunohistochemistry, with tissue microarray consisting of 128 surgically resected specimens; and scored using a semiquantitative method. The correlations between CSE1L expression and clinicopathological parameters were analyzed. RESULTS: CSE1L overexpression was associated with increased invasiveness and metastasis of cancer cells. Non-neoplastic colorectal glands showed minimal CSE1L staining, whereas most colorectal carcinomas (99.2%, 127/128) were significantly positive for CSE1L staining. Cytoplasmic CSE1L was associated with cancer stage (P=0.003) and depth of tumor penetration (P=0.007). Cytoplasmic CSE1L expression also correlated with lymph node metastasis of the disease in Cox regression analysis CONCLUSIONS: CSE1L regulates the invasiveness and metastasis of cancer cells, and immunohistochemical analysis of cytoplasmic CSE1L in colorectal tumors may provide a useful aid to prognosis.